Interpolation based predictive control by ellipsoidal invariant sets. (June 2020) - Rubin, Daniel; Mercader, Pedro; Gutman, Per-Olof; Nguyen, Hoai-Nam; Bemporad, Alberto
Abstract: A new interpolating control scheme for uncertain linear systems is developed. The interpolation is done between two saturated control laws, each given with its associated invariant set. A linear search is performed to compute a sub-optimal interpolation coefficient. Two algorithms are suggested — each incorporating a different optimization objective. The method guarantees robust stability and recursive feasibility, also in presence of persistent disturbances.